Respuesta :

i looked it up and it said it was c 

[tex]b=0[/tex] and [tex]b=4[/tex] is the solution for the equation[tex]\frac{5}{3b^3-2b^2-5} =\frac{2}{b^3-2}[/tex]

What is equation?

In mathematics, an equation is a formula that expresses the equality of two expressions, by connecting them with the equals sign =

According to question, we have the following equation:

[tex]\frac{5}{3b^3-2b^2-5} =\frac{2}{b^3-2}[/tex]

We have to find the solution.

We have the following equation:

[tex]\frac{5}{3b^3-2b^2-5} =\frac{2}{b^3-2}[/tex]

⇒[tex]5b^{3} - 6b^{3} = -4b^{2}[/tex]

⇒[tex]b^{2} (b - 4) = 0[/tex]

⇒[tex]b=0[/tex] and [tex]b=4[/tex]

Hence we can conclude that Option C is correct answer.

Learn more about solution for the equation here:

https://brainly.com/question/545403?referrer=searchResults

#SPJ2